Histopathological study after selenium toxicity in buffalo calves - GILL, G P S; ROY, K S; UPPAL, V (The Indian Journal of Animal Sciences, 2014)
Subacute selenosis was experimentally induced in 6 buffalo calves by oral administration of selenourea @ 0.75 mg/kg body weight. The calves died within 25 days. Clinical symptoms observed were loss of appetite and body weight; alopecia on tail and feet of animals. Congestion, inflammatory, haemorrhagic and necrotic changes in kidney, liver, lungs. skin, heart, duodenum, rumen, spleen, prescapular lymphnode and cerebrum were observed .